Large-Scale Experimental Validation of Real-Time Monitoring in Underground Gas Storage Wells Using Distributed Fiber Optic Sensing - Linqing Luo; Diana Abdulhameed; Gang Tao; Tianchen Xu; Jiangnan Wang; David Xu; Kenichi Soga; Yuxin Wu (IEEE Access)
Underground gas storage (UGS) is essential for balancing the natural gas supply and demand, but faces multiple risk factors, including well deformation and gas leaks. Current well investigation methods often require suspending operations, resulting in infrequent inspections and delayed detection of potential issues. This study investigated the sensitivity of distributed fiber optic sensing (DFOS) that integrates distributed temperature (DTS) and strain sensing (DSS) for well integrity monitoring without disturbing the well operations. Due to the impracticality of introducing risks to operational wells, laboratory simulated wellbore tests were conducted to simulate gas leak events and pressure cycles. These tests included temperature variation, gas leak detection, and accelerated cyclic pressure testing to simulate various UGS well operation environments and signals associated with leak events. To measure temperature and strain using a single optical fiber cable for installation simplicity, a new downhole optical fiber cable was designed. The results showed that the DFOS system could identify thermal events from gas injection and withdrawal operations, and leaks at tubing in old boreholes. It also successfully detected gas leaks through the cement behind the casing for newly constructed borehole, with a minimum leak rate of 1.5 LPM (Liter Per Minute). During simulated pressure cycles, the DFOS system detected small strain changes and minor tubing deformations, highlighting its potential for early detection of tubing failure. Additionally, the optical fiber remained intact after 500 pressure cycles demonstrating the robustness of the proposed installation method. These findings validate a new methodology for proactive real-time UGS well integrity management.